Soluble mediators of innate immunity in annelids and bivalve mollusks: A mini-review - Canesi, Laura; Auguste, Manon; Balbi, Teresa; Prochazkova, Petra (Frontiers in Immunology, 2022)
Annelids and mollusks, both in the superphylum of Lophotrochozoa (Bilateria), are important ecological groups, widespread in soil, freshwater, estuarine, and marine ecosystems. Like all invertebrates, they lack adaptive immunity; however, they are endowed with an effective and complex innate immune system (humoral and cellular defenses) similar to vertebrates. The lack of acquired immunity and the capacity to form antibodies does not mean a lack of specificity: invertebrates have evolved genetic mechanisms capable of producing thousands of different proteins from a small number of genes, providing high variability and diversity of immune effector molecules just like their vertebrate counterparts. This diversity allows annelids and mollusks to recognize and eliminate a wide range of pathogens and respond to environmental stressors. Effector molecules can kill invading microbes, reduce their pathogenicity, or regulate the immune response at cellular and systemic levels. Annelids and mollusks are “typical” lophotrochozoan protostome since both groups include aquatic species with trochophore larvae, which unite both taxa in a common ancestry. Moreover, despite their extensive utilization in immunological research, no model systems are available as there are with other invertebrate groups, such as Caenorhabditis elegans or Drosophila melanogaster, and thus, their immune potential is largely unexplored. In this work, we focus on two classes of key soluble mediators of immunity, i.e., antimicrobial peptides (AMPs) and cytokines, in annelids and bivalves, which are the most studied mollusks. The mediators have been of interest from their first identification to recent advances in molecular studies that clarified their role in the immune response.